La gestion des autorités traditionnelles par l’État namibien: le cas des Herero - Vincent Bertout (Cadernos de Estudos Africanos)
The integration of the traditional authorities into the organisation of the African state poses an acute problem. While they were until recently considered as an archaic survival or as the result of colonial manipulation which the post-colonial state did not want to recognise, these authorities become today essential for any effort to create local roots for the democratic state. This article inquires into the relations between the traditional leaders otjiherero and the elected representatives in Namibia. It demonstrates that the normalisation of the tradicional authorities remains difficult because of the inherited colonial relations which in this country have politicised the traditional leaders. Despite attempts by the administration at attributing a controlled space to the traditional authorities, these are today becoming more and more important in a context of political competition.